ANALISA MISREPRESENTASI DALAM PEMBENTUKAN STEREOTYPE PADA FILM DOKUMENTER - Musfiah Saidah; Ayu Setiyoningsih (Interaksi: Jurnal Ilmu Komunikasi, 2023)
The mass media through documentary films have an influence in constructing stereotypes of local culture. In the process of text and image representation, misrepresentation may occur, namely untruths or misrepresentations. This study aims to find out how local cultural stereotypes are shown in the documentary film Borneo's sea Bajou The Real Water World People. This film tells the story of the life of the Bajou people who are famous for their ability to survive in the water for a long time. This research is a qualitative research using Roland Barthes' Semiotics analysis method. The results show that in the documentary film Borneo's sea Bajou The Real Water World People there are signs that are represented causing misrepresentation through conversational texts and picture texts to support the local cultural stereotypes of the Bajou tribe.